Evaluasi Fungsionalitas Sistem Informasi Kerja Sama Politeknik Negeri Sriwijaya Menggunakan Black Box Testing - Della Oktaviany; Yunita Fauzia Achmad; Irma Salamah; Yeni Febriana; M Afiyah Tatumadha; M Ainul Chakra (Fakultas Teknik Universitas Hamzanwadi, 2026)
Collaboration management in higher education institutions requires an information system capable of supporting administrative processes, documentation, monitoring, and reporting in an integrated manner. Politeknik Negeri Sriwijaya’s Collaboration Information System was developed to manage proposal submission, verification, approval, document management, collaboration activity recording, and report preparation. This study aims to evaluate the system’s functionality using the Black Box Testing method by assessing the conformity between inputs and outputs without examining the program’s internal structure. Testing was conducted through 10 scenarios covering user login, collaboration proposal submission, verification, data revision, proposal approval and rejection, document uploading, activity input, monitoring, and reporting. Each scenario was evaluated by comparing the system’s actual output with the expected result. The results showed that all test scenarios produced outputs consistent with the expected results, achieving a success rate of 100%. These findings indicate that the system meets its primary functional requirements and is feasible for supporting more structured, centralized, documented, and integrated collaboration management at Politeknik Negeri Sriwijaya.